Antibody responses to a suite of novel serological markers for malaria surveillance demonstrate strong correlation with clinical and parasitological infection across seasons and transmission settings in The Gambia - Wu, Lindsey; Mwesigwa, Julia; Affara, Muna; Bah, Mamadou; Correa, Simon; Hall, Tom; Singh, Susheel K.; Beeson, James G.; Tetteh, Kevin K. A.; Kleinschmidt, Immo; D’Alessandro, Umberto; Drakeley, Chris (BMC medicine, 2020)
As malaria transmission declines, sensitive diagnostics are needed to evaluate interventions and monitor transmission. Serological assays measuring malaria antibody responses offer a cost-effective detection method to supplement existing surveillance tools. A prospective cohort study was conducted from 2013 to 2015 in 12 villages across five administrative regions in The Gambia. Serological analysis included samples from the West Coast Region at the start and end of the season (July and December 2013) and from the Upper River Region in July and December 2013 and April and December 2014. Antigen-specific antibody responses to eight Plasmodium falciparum (P. falciparum) antigens-Etramp5.Ag1, GEXP18, HSP40.Ag1, Rh2.2030, EBA175 RIII-V, PfMSP1 , PfAMA1, and PfGLURP.R2-were quantified using a multiplexed bead-based assay. The association between antibody responses and clinical and parasitological endpoints was estimated at the individual, household, and population level. Strong associations were observed between clinical malaria and concurrent sero-positivity to Etramp5.Ag1 (aOR 4.60 95% CI 2.98-7.12), PfMSP1 (aOR 4.09 95% CI 2.60-6.44), PfAMA1 (aOR 2.32 95% CI 1.40-3.85), and PfGLURP.R2 (aOR 3.12, 95% CI 2.92-4.95), while asymptomatic infection was associated with sero-positivity to all antigens. Village-level sero-prevalence amongst children 2-10 years against Etramp5.Ag1, HSP40.Ag1, and PfMSP1 showed the highest correlations with clinical and P. falciparum infection incidence rates. For all antigens, there were increased odds of asymptomatic P. falciparum infection in subjects residing in a compound with greater than 50% sero-prevalence, with a 2- to 3-fold increase in odds of infection associated with Etramp5.Ag1, GEXP18, Rh2.2030, PfMSP1 , and PfAMA1. For individuals residing in sero-positive compounds, the odds of clinical malaria were reduced, suggesting a protective effect. At low transmission, long-lived antibody responses could indicate foci of malaria transmission that have been ongoing for several seasons or years. In settings where sub-patent infections are prevalent and fluctuate below the detection limit of polymerase chain reaction (PCR), the presence of short-lived antibodies may indicate recent infectivity, particularly in the dry season when clinical cases are rare. Serological responses may reflect a persistent reservoir of infection, warranting community-targeted interventions if individuals are not clinically apparent but have the potential to transmit. Therefore, serological surveillance at the individual and household level may be used to target interventions where there are foci of asymptomatically infected individuals, such as by measuring the magnitude of age-stratified antibody levels or identifying areas with clustering of above-average antibody responses across a diverse range of serological markers.